Building community resilience in post-disaster resettlement in Pakistan. Issue 4 (29th August 2019) - Jamshed, Ali; Rana, Irfan Ahmad; McMillan, Joanna M.; Birkmann, Joern
Abstract : Purpose: The extreme flood event of 2010 in Pakistan led to extensive internal displacement of rural communities, resulting in initiatives to resettle the displaced population in model villages (MVs). The MV concept is quite new in the context of post-disaster resettlement and its role in building community resilience and well-being has not been explored. This study aims to assess the role of MVs in building the resilience of relocated communities, particularly looking at the differences between those developed by governmental and non-governmental organizations (NGOs). Design/methodology/approach: Four MVs, two developed by government and two by NGOs, were selected as case studies in the severely flood-affected province of Punjab, Pakistan. A sample of 145 households from the four MVs was collected using a structured questionnaire to measure improvements in social, economic, physical and environmental domains and to form a final resilience index. Supplementary tools including expert interviews and personal observations were also used. Findings: The analysis suggests that NGOs are more successful in improving the overall situation of relocated households than government. Core factors that increase the resilience of communities resettled by NGOs are provision of livelihood opportunities, livelihood skill development based on local market demand, training on maintenance and operation of different facilities of the MV and provision of extensive education opportunities, especially for women. Practical implications: The results of this study can guide policymakers and development planners to overcome existing deficiencies by including the private sector and considerations of socioeconomic development whenever resettling communities. Originality/value: In resilience discourse, resettlement of communities has been extensively debated based on qualitative arguments. This paper demonstrates an approach to quantify community resilience in a post-disaster resettlement context.